(untitled) (Modern Problems of Metallurgy, 2019)
Currently, the most widely used methods of finishing steel on the chemical composition through the processes of doping as a single additive, and complex master alloys for the formation of the desired properties of metal products. In order to obtain qualitatively new characteristics of chromium-nickel steels, it is necessary to expand the range of alloying additives used, taking into account the efficiency of their assimilation. Certainly, the selection of injected additives in steel refers to a complex multistage physicochemical process, which first of all should provide the conditions for the maximum degree of assimilation and uniform distribution of the seated master alloy with minimal energy and raw materials losses. The temperature factor is one of the most important catalysts for the assimilation of alloying, modifying and refining additives, the effectiveness of the reactions and the distribution of the leading elements between the metal and slag, as well as the most informative indicator for making decisions on the management of the temperature melting mode. Based on the structural features of metal melts, an idea was put forward on the approach to the choice of alloying additives with regard to their microheterogeneity. The paper proposed mathematical models for predicting liquidus and solidus temperatures of nickel-chrome steels using the concept of a targeted chemical bond. The research results are recommended for use in industrial conditions with the purpose of a scientifically-based selection of alloying elements and the directional formation of the final product, which will reduce energy costs by integrating the developed models into the process control system of steelmaking.